Mechanically strong and electrically conductive multilayer MXene nanocomposites. Issue 42 (21st October 2019) - Lipton, Jason; Weng, Guo-Ming; Alhabeb, Mohamed; Maleski, Kathleen; Antonio, Francisco; Kong, Jaemin; Gogotsi, Yury; Taylor, Andre D.
Abstract : A high-strength composite is formed by the hierarchical assembly of electrically conductive two-dimensional MXenes in a nacre-inspired structure. Abstract : Polymer nanocomposites offer the opportunity to bridge properties of nanomaterials to the macroscale. In this work, layer-by-layer (LbL) assembly is used to demonstrate nanocomposites of 2D titanium carbide nanosheets (MXene) and clay nanoplatelets (montmorillonite) to fabricate freestanding thin films with unique multifunctional properties. These thin films can be tuned by adjusting the thickness to exhibit a tensile strength of 138 MPa–225 MPa, EMI specific shielding effectiveness normalized to thickness and density up to 24 550 dB cm 2 g −1, and sheet resistance from 855 Ω sq −1 –3.27 kΩ sq −1 (corresponding to a range of conductivity from 53 S m −1 to 125 S m −1 ). This composite is the strongest MXene-based LbL film prepared to date, in part due to the nacre-like brick-and-mortar structure. Ultra-strong, multifunctional films of this nature are desirable for many applications ranging from membranes, to structural and multifunctional composites, energy harvesting and storage, and materials for aerospace.